The immunomodulatory role of tumor-initiating cells in digestive system tumors: from mechanisms to therapy - Zhang, Zun-yue; Zhang, Xin-feng; Xu, Cong-hui; Wang, Kun-hua; Huang, Fang (Frontiers in Immunology, 2025)
Targeting tumor-initiating cells (TICs) in digestive system tumors is a feasible strategy to boost the effectiveness of cancer immunotherapy. Because of their stem cell-like properties, TICs can cause tumor heterogeneity, recurrence, and resistance to conventional medicines, which can seriously impair treatment outcomes. This review discusses the unique features of TICs inside various digestive system tumors, such as colorectal, pancreatic, liver, and gastric cancers. We look at the mechanisms that TICs evade immune recognition, including altered tumor microenvironment, decreased immunogenicity, and immune checkpoint molecule expression. Furthermore, we highlight potential strategies for TICs, such as differentiation therapies, inhibiting certain signaling pathways, and enhancing immune recognition through advanced immunotherapeutic approaches. The analysis also examines the potential for combination therapy, which include adoptive cell therapies, TIC-targeted strategies, and immune checkpoint inhibitors. Lastly, we address the challenges presented by TIC heterogeneity and immune escape mechanisms, emphasizing the need for more clinical research to back up these innovative tactics. All things considered, TIC targeting is a significant method to improve immunotherapy’s efficacy in treating digestive system cancers, which will ultimately help patients.